Efforts to Improve Student Learning Outcomes on the Material Emulating the Struggle of the Prophet Muhammad, the Event of the Conquest of Mecca and the Farewell Pilgrimage at SD Negeri 152981 Tukka 1A - Sibuea, Erawati; Idawati (Journal of Media and Learning Technology, 2025)
This study aims to improve students' learning outcomes in the material "Emulating the Struggle of the Prophet: The Event of Fathu Makkah and Hajj Farewell" at SD Negeri 152981 Tukka 1A, Central Tapanuli Regency. The approach used in this study is classroom action research (CAR) which is carried out in two cycles, with a focus on improving students' understanding and involvement in the learning material. Data collection techniques are carried out through observation, learning outcome tests, and interviews. The results of the study indicate that the application of interactive and contextual learning methods has succeeded in increasing students' motivation and understanding of the material being taught. In the first cycle, the average value of students' learning outcomes was 70, while in the second cycle it increased to 85. Thus, it can be concluded that the use of an approach that is more oriented towards experience and learning based on Islamic values ​​can improve students' learning outcomes at SD Negeri 152981 Tukka 1A.